2013
DOI: 10.1016/j.ccr.2012.11.020
|View full text |Cite
|
Sign up to set email alerts
|

PGC1α Expression Defines a Subset of Human Melanoma Tumors with Increased Mitochondrial Capacity and Resistance to Oxidative Stress

Abstract: SUMMARY Cancer cells reprogram their metabolism using different strategies to meet energy and anabolic demands to maintain growth and survival. Understanding the molecular and genetic determinants of these metabolic programs is critical to successfully exploit them for therapy. Here, we report that the oncogenic melanocyte lineage-specification transcription factor MITF drives PGC1α (PPARGC1A) overexpression in a subset of human melanomas and derived cell lines. Functionally, PGC1α positive melanoma cells exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

50
677
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(739 citation statements)
references
References 49 publications
50
677
0
12
Order By: Relevance
“…Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref. 33) following treatment with vemurafenib, indicating that the drug may also be activating OxPhos in our model, in agreement with earlier findings (16,34).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref. 33) following treatment with vemurafenib, indicating that the drug may also be activating OxPhos in our model, in agreement with earlier findings (16,34).…”
Section: Discussionsupporting
confidence: 82%
“…Because HSF1 is required for several processes that involve normal cell proliferation, such as spleen cell proliferation following immunization (40), muscle regeneration (41), and postnatal growth in C57BL/6 mice (42), it is possible that PGC-1α induction by fasting in liver (4) and muscle (43) represses HSF1 to mediate some of the antiproliferative effects of fasting. These scenarios also may hold true in cancer cells, although the potential effect of PGC-1α on cancer cell growth and survival is controversial, with reports suggesting both positive (44,45) and negative (46)(47)(48)(49)(50) associations between PGC-1α activity and cancer cell survival [including a negative association in HepG2 cells (51)], depending on the cellular context and on PGC-1α expression levels. It thus is possible that PGC-1α effects in cancer depend on a balance between its ability to induce metabolic genes and oxidative stress-response genes, a property that may promote cancer growth, and its ability to repress HSF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, IMP2-positive glioma and PPARGC1A (PGC1a)-positive melanoma showed tumor progression associated with mitochondrial energy activation in the absence and presence of enhanced ROS levels, respectively. 39,40 Thus, despite the general enhancement of glycolytic bioenergetic requirements in many cancers (so called as "Warburg effect"), several recent studies have revealed unanticipated tumor metabolism by Warburg, that is, the bioenergetic type of tumors can vary widely from glycolysis to OXPHOS. [41][42][43][44] Our findings suggest that OXPHOS-mediated metabolic activation provides a bioenergetic source to promote leukemogenesis in Fbxl10-upregulated HSCs.…”
Section: Discussionmentioning
confidence: 99%